Manajemen Pengembangan Kurikulum Pondok Pesantren dalam Membentuk Karakter Religius Santri di Pondok Pesantren Al Fatah Singkawang - Raden Roro Dinul Qoyyimah; Ubabuddin Ubabuddin; Sri Sunantri (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to describe and analyze the curriculum development management of Al-Fatah Islamic Boarding School in Singkawang, including planning, implementation, and evaluation, as well as its impact on the formation of religious character of students. The background of this study is the strategic role of the Islamic boarding school curriculum as the heart of education in integrating Islamic values ​​and life skills to produce a generation with noble character amidst the challenges of modernity. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the Head of the Boarding School, the Chairperson and Staff of the Student Care Council, Subject Teachers, and representatives of class XII students. The results of the study indicate that the curriculum development management at Al-Fatah Islamic Boarding School in Singkawang has been implemented through systematic stages, starting from needs analysis to evaluation, with the main considerations being the values ​​of Islamic teachings, the objectives of Islamic boarding school education, and the needs of students. First, in the planning aspect, the curriculum is prepared through deliberation and has integrated Islamic values, although there are obstacles such as differences of opinion among staff and minimal involvement of students in the initial formulation process. Second, the curriculum is implemented in an integrated manner, integrating formal learning with boarding school activities (practicing religious practices such as congregational prayer, tadarus (recitation of the Koran), and dhikr (remembrance of God).